Docking based strategies for the validation of deep learning generative models - And the search for novel ligands for A2aR, JAK2, KOR AND USP7. - Avila, Henrique de Vasconcellos (2022)
Dissertação de Mestrado em Bioquímica apresentada à Faculdade de Ciências e Tecnologia